2011
DOI: 10.3763/ijas.2010.0563
|View full text |Cite
|
Sign up to set email alerts
|

The Rakai chicken model: an approach that has improved fortunes for Ugandan farmers

Abstract: Poverty is widespread in Rakai district, which had been badly affected by HIV/AIDS resulting in many orphan-headed households. A poultry improvement programme based on local practices and cross-breeding indigenous chickens was desired by the communities to improve their income. Partnerships for implementation were strategically chosen. Scaling out was realized through participatory approaches, use of trainers from the communities, establishment of the Rakai Chicken Breeders Association, commercially and locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 2 publications
0
16
2
Order By: Relevance
“…Meanwhile the mean bodyweight of the chickens studied ranged from 1.65 kg to 2.39 kg at 44 weeks old. This is lighter than the values reported by Islam et al (2014) and Roothaert et al (2011)in the Varanaja and Rakai indigenous chicken breeds of India and Uganda, respectively. A value of 2.98 kg was reported at 40 weeks for Vanaraja reared extensively, and 2.5 kg at 45 weeks for the Rakai when reared extensively.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Meanwhile the mean bodyweight of the chickens studied ranged from 1.65 kg to 2.39 kg at 44 weeks old. This is lighter than the values reported by Islam et al (2014) and Roothaert et al (2011)in the Varanaja and Rakai indigenous chicken breeds of India and Uganda, respectively. A value of 2.98 kg was reported at 40 weeks for Vanaraja reared extensively, and 2.5 kg at 45 weeks for the Rakai when reared extensively.…”
Section: Discussioncontrasting
confidence: 53%
“…Similarly, Khawaja et al (2012) reported average egg weights of 44.42 g, 43.35 g, and 56.83 g for Desi, Fayoumi and Rhode Island Red (RIR) breeds of chicken, respectively, reared up to 72 weeks old, which were comparatively lower than values recorded by the Boschveld chickens. Although the Boschveld birds came into lay at 21 weeks old (147 days), the Varanaja, an indigenous breed of India, and the Rakai, an indigenous breed of Uganda, came into lay at 187.45, 201.31 and 154 days, respectively (Islam et al, 2014;Roothaert et al, 2011). This shows that Boschveld chickens come into lay earlier than the breeds reported by Islam et al ( 2014) and Roothaert et al (2011).…”
Section: Discussioncontrasting
confidence: 36%
See 3 more Smart Citations